Comparison of phenolics, flavonoids, and cellular antioxidant activities in ear sections of sweet corn (Zea mays L. saccharata Sturt). Issue 1 (17th December 2018) - Yang, Tianran; Guang Hu, Jian; Yu, Yongtao; Li, Gaoke; Guo, Xinbo; Li, Tong; Liu, Rui Hai
Abstract: This study aims to evaluate phenolics, flavonoids, total and cellular antioxidant activity (CAA), antioxidant capacity in ear sections of sweet corn. Corn cob and mature corn silk showed the highest contents of total phenolics and flavonoids ( p <  0.05), respectively. Gallic acid and ferulic acid were the main free and bound phenolics in each ear part of corn, respectively ( p <  0.05). Corn resident (CR) had a dominant role in total antioxidant activity and cellular antioxidant activity (CAA) ( p  < 0.05). Considering all the antioxidant properties, CR showed the best performance. The content of ferulic acid was correlated closely with CAA ( R 2 = 0.898, p  < 0.05) and total antioxidant capacity ( R 2 = 0.971, p  < 0.05), and total antioxidant capacity was also connected tightly with total phenolics ( R 2 = 0.886, p  < 0.05). The results of this investigation were significant to enhance recognition and application of ear sections in food industry. Practical applications: Sweet corn is widely cultivated in Asia, America, and other regions for fresh or industrial food because of high sugar, dietary fiber, and vitamins. However, there is no systematic assay on ear sections of sweet corn concerning antioxidant evaluation. The study investigated phytochemical profiles and antioxidant capacity in ear sections of sweet corn systematically, and made a comprehensive comparison of them combined with correlation analysis. The results indicated that ear sections of sweet corn, not only kernels, demonstrated high antioxidant capacity. Ear sections show promising potential application in food industry.